2018
DOI: 10.1007/s00392-018-1251-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of bivalirudin for percutaneous coronary intervention in acute coronary syndromes: a meta-analysis of randomized-controlled trials

Abstract: Compared with heparin, bivalirudin was associated with a similar incidence of ischemic events following PCI for ACS. An association of bivalirudin with decreased bleeding was not seen with balanced use of GPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 31 publications
2
7
0
2
Order By: Relevance
“…More recently, a meta-analysis updated for the results of VALIDATE-SWEDEHEART confirmed that bivalirudin compared with heparin was associated with a similar incidence of all-cause death and ischaemic events after PCI for ACS. 710 A significant association of bivalirudin with decreased risk of bleeding was only found with unbalanced use of GP IIb/IIIa inhibitors in conjunction with heparin. In summary and based on the above-mentioned trials, UFH is primarily recommended as an anticoagulant for PCI.…”
Section: Peri-interventional Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a meta-analysis updated for the results of VALIDATE-SWEDEHEART confirmed that bivalirudin compared with heparin was associated with a similar incidence of all-cause death and ischaemic events after PCI for ACS. 710 A significant association of bivalirudin with decreased risk of bleeding was only found with unbalanced use of GP IIb/IIIa inhibitors in conjunction with heparin. In summary and based on the above-mentioned trials, UFH is primarily recommended as an anticoagulant for PCI.…”
Section: Peri-interventional Treatmentmentioning
confidence: 99%
“…IIa C Bivalirudin (0.75 mg/kg bolus, followed by 1.75 mg/kg/h for up to 4 h after the procedure) may be considered as an alternative to UFH. 163,708,710,714,728 IIb A…”
Section: Iia Bmentioning
confidence: 99%
“…Previous record demonstrated that STEMI and NSTEMI groups are semblable in the efficacy. 27 With regards to stent thrombosis, we found no significant difference in the STEMI group. However, we cannot draw definitive conclusions because only a small number of trials have studied stent thrombosis.…”
Section: Discussionmentioning
confidence: 57%
“…In percutaneous coronary artery interventions (PCI) and transcatheter aortic valve replacements (TAVR), multiple studies have provided evidence on the comparable efficacy of heparin and bivalirudin as intraprocedural anticoagulants (9,10). A trend towards the lower incidence of access or non-access hemorrhagic complications has also been indicated in several literature pieces, but this is not universally acknowledged (11,12). This has led to an interest in investigating whether the use of bivalirudin can also provide another option of intraprocedural pharmacology in LAAO.…”
Section: Introductionmentioning
confidence: 99%